2022
DOI: 10.1136/neurintsurg-2021-018551
|View full text |Cite
|
Sign up to set email alerts
|

Rupture risk prediction of cerebral aneurysms using a novel convolutional neural network-based deep learning model

Abstract: BackgroundCerebral aneurysms should be treated before rupture because ruptured aneurysms result in serious disability. Therefore, accurate prediction of rupture risk is important and has been estimated using various hemodynamic factors.ObjectiveTo suggest a new way to predict rupture risk in cerebral aneurysms using a novel deep learning model based on hemodynamic parameters for better decision-making about treatment.MethodsA novel convolutional neural network (CNN) model was used for rupture risk prediction r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…In their study, the AUC in the CNN was 0.76, which was better than that obtained by a human evaluator (AUC: 0.54). The DLM based on hemodynamic parameters also had good predictive accuracy in assessing IA rupture risk ( 34 ). However, these studies only included anterior circulation IAs, and the results may not be applicable to other IA sites.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, the AUC in the CNN was 0.76, which was better than that obtained by a human evaluator (AUC: 0.54). The DLM based on hemodynamic parameters also had good predictive accuracy in assessing IA rupture risk ( 34 ). However, these studies only included anterior circulation IAs, and the results may not be applicable to other IA sites.…”
Section: Discussionmentioning
confidence: 99%
“…34 Nevertheless, several hemodynamic studies have used FSI analysis. [35][36][37] Cho et al 35 suggested in FSI analysis that strain was more effective than WSS in predicting the rupture risk of cerebral aneurysms. In addition, unlike WSS, which shows inconsistency as it pregresses from formation to growth and rupture, high strain continues to be involved in the natural history of cerebral aneurysms.…”
Section: Another Hemodynamic Studymentioning
confidence: 99%
“…The deep shape learning method could achieve the highest accuracy of 0.82. Yang et al ( 20 ) utilized CNN on hemodynamic factors of WSS and strain to predict the rupture risk of cerebral aneurysms, and the best AUC was up to 0.883.…”
Section: Introductionmentioning
confidence: 99%